Sanksi Pidana Pelaku Promosi Judi Online Dalam Putusan Nomor: 19/Pid.Sus/2024/Pn Smd Perspektif Hukum Pidana Islam - Abdul Kholik, Muhamad; Rahmat, Ariz Abiyyu; Maulana, Ade; Joli, Angelika; Rizkiansyah, Aprila (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2025)
This research is motivated by the rampant phenomenon of online gambling promotion in Indonesia, which is not only carried out by celebrities but also ordinary people due to economic motivation. One of the cases that is the focus of the study is Decision Number: 19/Pid.Sus/2024/Pn Smd which imposes criminal sanctions on a perpetrator of online gambling promotion through social media. This topic is important because the high number of online gambling users, including among school-age children, indicates a serious threat to morality and social order. This research uses a normative juridical method with a library research approach to examine the legal basis and considerations of judges, as well as reviewing the suitability of criminal sanctions in the perspective of Islamic criminal law. The results show that the criminal elements have been legally fulfilled according to positive law, and the defendant's actions are also included in the jarimah ta'zir category in Islamic law. Although the verdict is considered complete in terms of evidence, the weakness lies in the lightness of the sanction which is only a conditional sentence, which risks creating a weak deterrent effect. Therefore, the results of this study are important as evaluation material for the development of legal policies that are more responsive and based on substantive justice values, both in terms of national law and Islamic perspectives.